Exploring Concept of Sustainability through Understanding Traditional Resource Management Practices: Case of Thar Desert, India. (June 2019) - Ghosh Saxena, D
Abstract: The Brundtland Report published in 1980s, for the United Nations Organization, mentioned the concept of sustainability for the first time. It explained the concept as it is understood in modern times. However, while the term itself may not be very old, but is the core idea of sustainability and sustainable development also so recent? Or has it been central to the historic cities and developments which have managed to survive for centuries. Following paper examines various components, principles and parameters of sustainability, as defined in contemporary discourse, in a specific geographical context. The background is set in Indian subcontinent's desert landscape- Thar, an arid and semi-arid geographic region. It explores knowledge systems developed and still practiced by native communities, over generations, to brave tough climatic condition and have shaped unique habitat in this/such resource parched geographies. The paper highlights the core values of sustainability as understood by the native communities of Thar and the nature of development it eventually shaped here as a product of this understanding. Finally, it concludes the merits in taking clues from traditional practices of resource management and strengthening the role of communities towards a more sensitive and sustainable future.